Response of 1,5‐anhydroglucitol level to intensive glucose‐ and blood‐pressure lowering interventions, and its associations with clinical outcomes in the ADVANCE trial - Selvin, E; Wang, D; McEvoy, JW; Juraschek, SP; Lazo, M; Hamet, P; Cooper, ME; Marre, M; Williams, B; Harrap, S; Chalmers, J; Woodward, M (Wiley, 2019)
Aims To evaluate 1,5‐anhydroglucitol (1,5‐AG) according to clinical outcomes and assess the effects of glucose‐ and blood pressure‐lowering interventions on change in 1,5‐AG levels in people with type 2 diabetes.